Climate Change In Colombia: Trends And Perspective to Achieve Sustainable Development - Pardo Martínez, Clara Inés (European Journal of Sustainable Development, 2018)
Colombia is recognized as a country that has at high-risk and vulnerability from climate change impacts, which can affect diverse human settlements, development and economic activities. Hence, in rural areas the main challenges are the means of living and food production, whereas, in urban contexts climate change should decrease heath conditions and quality of life. This research seeks to analyse and evaluate trends and perspectives of climate change in Colombia in the last decade using qualitative and quantitative methods that allow to determine whether in this country climate governance has contributed to the mitigation and adaptation to climate change, especially in vulnerable areas that are more likely to poverty. Results indicate that in the up coming 15 years in the most areas of the country the temperature will increase 1°C which should undermine development especially in poor and rural areas. Despite quite a climate governance, it is necessary to strength its application and to raise awareness about importance to promote sustainable development from housing to the productive sector to achieve mitigation and adaptation to decrease and control risks by new weather conditions. All findings of this study are important for policy makers and local government to improve the mechanisms to adapt and mitigate climate change in Colombia where climate change should increase poverty and inequality. Keywords: Climate change, perception, qualitative and quantitative analysis, Colombia